(untitled) (Research, Society and Development, 2021)
Introduction: The increase in obesity has been registered in all age groups. This pandemic, considered the disease of the century, directly affects public health on all continents and represents a complex challenge for modern society. Objective: To compare weight loss in adolescents undergoing a multiprofessional obesity treatment program (PMTO) with and without the monitoring of their mothers. Method: Eleven adolescents, aged between 13 and 17 years, of both sexes, were overweight or obese. All participants signed the Free and Informed Consent Form (ICF), before beginning their participation. All indicated having availability and interest to participate in interventions with activities in the aquatic environment, three times a week, followed by an hour of theoretical guidance with professionals in the areas of Physical Education, Nutrition and Psychology. Anthropometric assessments were carried out, following standardized procedures, the variables were collected in the pre-test and post-test, after 16 weeks of a PMTO. Results: The adolescents showed improvements both in the first semester and in the second semester, when they were accompanied by their mothers. However, in the first semester, significant improvements (p <0.05) were observed in a greater number of variables, such as WC (p = 0.0389), absolute fat (p = 0.0005) and fat percentage (p = 0.0009). In the second semester they showed significant improvements (p <0.05), in the percentage of fat and in resting HR. Conclusion: Participation in PMTO in the aquatic environment promoted improvements in the physical fitness of adolescents, both when they were accompanied by their mothers, and in their absence.